Column‐Compound Extremes in the Global Ocean - Joel Wong; Matthias Münnich; Nicolas Gruber (AGU Advances, 2024)
Abstract Marine extreme events such as marine heatwaves, ocean acidity extremes and low oxygen extremes can pose a substantial threat to marine organisms and ecosystems. Such extremes might be particularly detrimental (a) when they are compounded in more than one stressor, and (b) when the extremes extend substantially across the water column, restricting the habitable space for marine organisms. Here, we use daily output of a hindcast simulation (1961–2020) from the ocean component of the Community Earth System Model to characterize such column‐compound extreme events (CCX), employing a relative threshold approach to identify extremes and requiring them to extend vertically over at least 50 m. The diagnosed CCX are prevalent, occupying worldwide in the 1960s about 1% of the volume contained within the top 300 m. Over the duration of our simulation, CCX become more intense, last longer, and occupy more volume, driven by the trends in ocean warming and ocean acidification. For example, the triple CCX expanded 39‐fold, now last 3‐times longer, and became 6‐times more intense since the early 1960s. Removing this effect with a moving baseline permits us to better understand the key characteristics of CCX, revealing a typical duration of 10–30 days and a predominant occurrence in the Tropics and high latitudes, regions of high potential biological vulnerability. Overall, the CCX fall into 16 clusters, reflecting different patterns and drivers. Triple CCX are largely confined to the tropics and the North Pacific and tend to be associated with the El Niño‐Southern Oscillation.